Epoxy Enhanced Polyethersulfone Membrane For Removal Of Chromium - Johan, Erniza Mohd (2017)
The present work attempted to remove carcinogenic Cr(VI) ions from aqueous solution using Bisphenol A Diglycidyl Ether, (DGEBA) and Polyethersulfone (PES), (DGEBA–PES) blended membrane prepared through dry-wet phase inversion for ultrafiltration process. The changes in physical properties were measured using Field emission scanning electron microscopy (FESEM), mean pore size measurement and porosity measurement. The results confirmed the significant changes of pores connectivity between the sub-layers of the blend membranes as the synthesis parameters (PES composition, DGEBA compositions and duration of dry-phase inversion) were manipulated. The DGEBA–PES blend membranes also demonstrated an enhanced membrane hydrophilicity when DGEBA resin was introduced into the PES polymer matric. The Cr ions activity at different pH was first analyzed, where the amount of Cr(VI) was found to be higher in alkaline solution (pH > 7). When the epoxy resin was manipulated at fixed 15 wt.% polymer compositions, the blended DGEBA-PES membranes with 10 wt.% DGEBA revealed rejection of Cr(VI) ions at 53% without jeopardizing the permeate flux (12.17 L/m2h) . On the other hand, 18 wt.% PES gave the Cr(VI) rejection at 62% with acceptable permeate flux at 22.09 L/m2h when the amount of PES polymer was manipulated. In present work, the blended membrane (18 wt. % PES polymer with 30 wt.% DGEBA) has successfully demonstrated Cr(VI) ion rejection at 90% with permeate flux of 21.06 L/m2h for dead-end filtration and 93% rejection with 5.40 L/m2h permeate flux for cross flow filtration when the polyethylenimine (PEI) was introduced into the feed solution. In this work, DGEBA–PES membrane synthesized through 1 hour of dry phase inversion showedthe best performance of Cr(VI) rejection at 88.84% with steady permeation flux of 11.27 L/m2hr for cross-flow filtration. Fouling mechanism on dead end filtration membrane was also studied using Hermia’s fouling models where the DGEBA-PES membranes were generally fouled by complete/ internal pore blocking, followed by the cake formation mechanism at the end of the process. From the results, it can be conclude that the DGEBA-PES membrane has a great potential in the removal of carcinogenic Cr(VI) ions from the polluted waste stream. With the fouling mechanism study, membrane with better separation performance can be designed.